Management of Amniotic Fluid Embolism (AFE) using anticoagulation-free ECMO - Yan, Peijie; Sun, Chuihua; Ma, Xiaoyan; Sun, Xin; Wang, Liming; Zhang, Qinghai (Zeitschrift für Geburtshilfe und Neonatologie, 2025)
Amniotic fluid embolism (AFE) is a critical obstetric complication characterized by the entry of amniotic fluid and its components into maternal circulation during parturition, leading to acute cardiopulmonary failure, disseminated intravascular coagulation (DIC), and anaphylactic shock. Affected patients typically exhibit abrupt onset, rapid progression, and exceedingly high mortality. Early recognition and prompt intervention are pivotal in AFE management. We present a case of AFE-induced cardiac arrest in a 35-year-old primigravida who developed acute cardiopulmonary collapse during vaginal delivery, followed by cardiac arrest. After cardiopulmonary resuscitation, massive transfusion, and crash emergency cesarean section, anticoagulant-free venoarterial extracorporeal membrane oxygenation (VA-ECMO) was initiated. Subsequent multimodal therapies – including aggressive transfusion support, uterine artery embolization for hemostasis, exploratory laparotomy, and targeted DIC management – ensured safe ECMO maintenance without device-related complications. By hospital day 3, hemodynamic and respiratory stability were achieved, enabling successful ECMO weaning. This case highlights that ECMO remains a viable therapeutic option for salvaging critically ill AFE patients with refractory hemorrhagic shock, DIC, and cardiopulmonary failure.
Keywords: Amniotic Fluid Embolism; disseminated intravascular coagulation; VA-ECMO; anticoagulation-free